First-Principles Density Functional Theory Calculations of Bilayer Membranes Heterostructures of Ti(3)C(2)T(2) (MXene)/Graphene and AgNPs - Berdiyorov, Golibjon. R. (Membranes (Basel), 2021)
The properties of two-dimensional (2D) layered membrane systems can be medullated by the stacking arrangement and the heterostructure composition of the membrane. This largely affects the performance and stability of such membranes. Here, we have used first-principle density functional theory calculations to conduct a comparative study of two heterostructural bilayer systems of the 2D-MXene (Ti(3)C(2)T(2), T = F, O, and OH) sheets with graphene and silver nanoparticles (AgNPs). For all considered surface terminations, the binding energy of the MXene/graphene and MXene/AgNPs bilayers increases as compared with graphene/graphene and MXene/MXene bilayer structures. Such strong interlayer interactions are due to profound variations of electrostatic potential across the layers. Larger interlayer binding energies in MXene/graphene systems were obtained even in the presence of water molecules, indicating enhanced stability of such a hybrid system against delamination. We also studied the structural properties of Ti(3)C(2)X(2) MXene (X = F, O and OH) decorated with silver nanoclusters Ag(n) (n ≤ 6). We found that regardless of surface functionalization, Ag nanoclusters were strongly adsorbed on the surface of MXene. In addition, Ag nanoparticles enhanced the binding energy between MXene layers. These findings can be useful in enhancing the structural properties of MXene membranes for water purification applications.